Management of tourist values on the example of the Mstów commune - Wolski, Oskar; Różycki, Paweł (Geotourism/Geoturystyka)
The management of tourist values is not an easy issue. I It seems that the presence of specific cultural premises, exceptional landscapes and landforms is sufficient to attract tourists. Unfortunately, this is a very complex problem, requiring numerous treatments, knowledge and skills of decision-makers. Development trends of communes, towns and entire regions are determined by various issues, sometimes independent on the will of the residents and local authorities. The key issue seems to be finances. Before a tourism product is developed and it appears in the minds of tourists, and before the area becomes a real tourism region, the expenses must be incurred for ’ development and promotion of attractions. An example of the commune having aspirations for tourism development is Mstów located in the vicinity of Częstochowa. Location and diversified tourist offer in the future can be the magnets for tourists coming to Częstochowa or traveling through the northern part of the Kraków-Częstochowa Upland. It is also important to develop new tourist trails in the area of commune. Also, support from the government, even without significant funding at the moment, is an important stimulus for the development of various forms of tourism.